Bilingualism: Diglossia and Code-Switching to Indonesian Scholars - Arjulayana Arjulayana (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Code switching and Diglossia’s population can be found in variety places, both formal and informal places. This paper is aimed to report the data analysis relate with diglossia and code switching which is happen to Indonesian Scholar. For many reasons diglossia and code switching are parts of language varieties, and as the unique Indonesian characteristics, because not all countries are getting diglossia phenomenon. It happened only for country that has high and low languages use in their daily interaction. This belief assumes that diglossia and code switching as the varieties of language can be adapted to foster learner’s ability, creativity, and awareness in practicing their language. The study is uses qualitative approach, with descriptive analysis. The purposive sampling is used to gain the data, with 5 questions in short answer form, and 5 questions with close ended question-answer to 16 higher students of 2nd semester from University of Muhammadiyah Jakarta majoring of religious education department. This research uses triangulation to know the validity of the data. The result of this research shows; firstly, bilingualism is a language varieties and happened in Indonesia with highest code-switching population can advocate Indonesia scholar to conserve one of local wisdom, and language varieties.  Secondly, bilingual is familiar to Indonesian Scholar, because most of Indonesian scholars have their own local language. This also shown from their status in some social medias, way of interact; daily language uses, and etc. Thirdly, practicing bilingual is fun, and it could be good habit for them, because in special condition, sometimes their own language helps them to melt the situation in conversation context